Political philosophy from Plato to Mao - Cohen, Martin (Pluto Press, 2001)
This introduction to political philosophy explores the history of ideas and ways of thinking about society. Beginning with Plato's "Utopia", Cohen goes on to discuss political philosophies from Niccolo Machiavelli's "Psychology of the State" through to Hobbes' "Wicked World".